Diagnostic Performance of Linked Color Imaging Compared to White Light Imaging During Secondary Endoscopic Evaluation in Patients with Gastric Neoplasia Referred for Endoscopic Resection: A Randomized Comparative Study - Lee, Jae Gon; Yoo, In Kyung; Lee, Sang Pyo (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Linked color imaging (LCI) has been shown to improve the visibility of gastric lesions and may enhance the detection of gastric superficial neoplasia (GSN). The aim was to compare the detection performance of LCI versus white light imaging (WLI) in patients referred for endoscopic resection of GSNs. Materials and Methods: In this randomized prospective comparative study, patients who were referred for endoscopic resection of gastric adenoma or early gastric cancer (ECG) were assigned to either the LCI or WLI group. Initial endoscopic evaluation was performed using the assigned mode (LCI or WLI), followed by a second examination using the alternate mode. The primary outcome was detection sensitivity for GSNs. Results: Ninety-five patients with 104 lesions were analyzed: 48 in the LCI group and 47 in the WLI group. Detection sensitivity at first observation was 94.23% in the LCI group and 86.54% in the WLI group (P = .122). The mean tumor detection time was significantly shorter in the LCI group (54.2 ± 38.4 seconds) than in the WLI group (74.0 ± 55.5 seconds; P = .049). Tumors with type IIb morphology were significantly more likely to be missed than tumors with other morphologies (P = .014). Conclusion: Linked color imaging may improve lesion detection performance and efficiency during the endoscopic evaluation of GSNs. Cite this article as: Lee JG, Yoo IK, Lee SP, et al. Diagnostic performance of linked color imaging compared to white light imaging during secondary endoscopic evaluation in patients with gastric neoplasia referred for endoscopic resection: A randomized comparative study. Turk J Gastroenterol. Published online: August 11, 2025. doi 10.5152/tjg.2025.24821